(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: To describe the current status of construction, use and maintenance of latrines of Xo Dang ethnic minority people in Mang Ri commune, Tu Mo Rong district, Kon Tum province and some associated factors. Methods: Applying descriptive cross-sectional study design, combining quantitative and qualitative research. The implementation period was from January 2022 to the end of May 2022. Results: 118 household heads agreed to participate in the study. The coverage of latrines reached 90.7%; the rate of hygienic latrines on construction 50.0%; the rate of latrines that were suitable for use and storage was 38.1% and the rate of general hygienic latrines accounted for 34.7%. Some factors related to the situation included gender, occupation of the household heads; economic conditions; knowledge about hygienic latrines and latrine-related diseases; access to information; sanitary supply service; access to skilled masons; matching construction costs with the family economy and policies to support the construction of latrines.